Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1440-1789.2007.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

The value and correlation between PRL‐3 expression and matrix metalloproteinase activity and expression in human gliomas

Abstract: Local invasion of tumor cells is characteristic of most human glioma invasions. It is associated with increased motility and a potential to degrade the extracellular matrix. Matrix metalloproteinases (MMPs) have been proved to be a main process in local invasion of brain tumor. PRL-3 is a new protein tyrosine phosphatase which would also degrade the extracellular matrix and has been proved to be expressed in liver metastases derived from colorectal cancer. In this study, we sought to investigate the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
(15 reference statements)
3
30
0
Order By: Relevance
“…PRL-3 is amplified and overexpressed in CRC metastases compared with primary tumors, and its expression correlates with metastasis in other tumor types. 8,[11][12][13][14][15][16] In this report, PRL-3 induced cell migration and invasion in a human colon cancer-derived cell system (DLD-1 cells) and enhanced DLD-1 cell motility. It is consistent with previous studies with other cancer cell lines.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…PRL-3 is amplified and overexpressed in CRC metastases compared with primary tumors, and its expression correlates with metastasis in other tumor types. 8,[11][12][13][14][15][16] In this report, PRL-3 induced cell migration and invasion in a human colon cancer-derived cell system (DLD-1 cells) and enhanced DLD-1 cell motility. It is consistent with previous studies with other cancer cell lines.…”
Section: Discussionmentioning
confidence: 70%
“…This result is consistent with previous reports showing that the function and localization of PRL-3 can be inhibited by FPTase inhibitors and regulated by MMP expression in other cell types. 3 Although it has been reported that MMP-2 and -14 cooperatively contribute to PRL-3-dependent invasion of gliomas, 16 the expression level of MMP-14 mRNA was very high, and its expression was dramatically downregulated by the FPTase inhibitor in DLD-1 (PRL-3) cells. However, overexpression of MMP-14 in the cells did not effect on migration of the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity has been documented both in vivo and in vitro (Martin & Matrisian, 2007). The pro-invasive activity of MT1-MMP has been associated by some authors with invasion and progression in other tumors, such as neck tumors by Zhai et al (2005) and astrocytic tumors by Forsyth et al (1999);Nakada et al (1999Nakada et al ( , 2001 and Kong et al (2007). Among the studies that have found a direct relationship between the increased expression of MT1-MMP and the evolution of gliomas, that of Nuttall et al (2003) stands out because it found a greater than 21-fold increase in the level of MT1-MMP mRNA in glioblastomas relative to non-tumor brain tissue.…”
Section: Wwwintechopencommentioning
confidence: 92%
“…Among human tumor tissues, PRL-3 was first identified to be specifically overexpressed in liver metastases derived from colorectal cancer using serial analysis of gene expression (SAGE) technology (9), and subsequently an accumulating number of studies demonstrated PRL-3 overexpression in various tumor types (10)(11)(12)(13)(14). Enforced PRL-3 expression can promote invasion, migration, and angiogenesis in cell culture and mouse model systems (15)(16)(17)(18)(19), whereas knockdown of endogenous PRL-3 by small interfering RNA (siRNA) or transfection with catalytically inactive mutants can abrogate these properties (11,20,21).…”
Section: Introductionmentioning
confidence: 99%